TOWARDS SPATIAL INFORMATION SYSTEM ADOPTION USING EXTENDED TAM AND IS SUCCESS MODEL - Anjani, Heni; Inan, Dedi I.; Juita, Ratna; Sanglise, Marlinda (STMIK Royal, 2024)
Abstract: By leveraging digital technology, Laporkitong enhances transparency and accountability, as well as facilitates public participation in the oversight and enforcement processes related to land use and natural resource management. The Laporkitong website functions as an online reporting application aimed at documenting instances of spatial planning violations in the West Papua Province. The lack of public knowledge about the Laporkitong application has led to numerous issues. Therefore, an analysis of the adoption of the Laporkitong application is necessary. This study aims to investigate the influence of Perceived Quality, Perceived Control, and Perceived Ease of Use factors as determinants of the residents' willingness to use the Laporkitong application, employing the Technology Acceptance Model (TAM) and DeLone and McLean IS Success (IS D&M) theories. As many as 160 valid respondents are gathered based purposive sampling technique and evaluated using Partial Least Square Structural Equation Modeling (PLS-SEM). The results inform that all seven hypotheses are accepted with the R-square of the intention to use is 0.273 indicationg 27.3% variance of the model can determine the outcome. Further discussion and conclusion regarding the implication of theoretical and practical contribution are also discussed. Keywords: laporkitong; perceived control; perceived ease of use; perceived quality; technology acceptance model Abstrak: Dengan memanfaatkan teknologi digital, Laporkitong meningkatkan transparansi dan akuntabilitas, serta memfasilitasi partisipasi publik dalam proses pengawasan dan penegakan terkait penggunaan lahan dan pengelolaan sumber daya alam. Website Laporkitong berfungsi sebagai aplikasi pelaporan online yang bertujuan untuk mendokumentasikan pelanggaran perencanaan tata ruang di Provinsi Papua Barat. Minimnya pengetahuan masyarakat terhadap aplikasi Laporkitong menyebabkan banyak permasalahan. Maka dari itu perlu dilakukan analisis mengenai adopsi pada aplikasi Laporkitong. Penelitian ini bertujuan untuk menyelidiki pengaruh faktor Kualitas yang Dirasakan, Kendali yang Dirasakan, dan Kemudahan Penggunaan yang Dirasakan sebagai penentu keinginan penduduk untuk menggunakan aplikasi Laporkitong, dengan menggunakan Model Penerimaan Teknologi (TAM) dan teori Kesuksesan Sistem Informasi (IS D&M) DeLone dan McLean. Sebanyak 160 responden valid dikumpulkan berdasarkan teknik purposive sampling dan dievaluasi menggunakan Partial Least Square Structural Equation Modeling (PLS-SEM). Hasilnya menunjukkan bahwa semua tujuh hipotesis diterima dengan R-square niat untuk menggunakan adalah 0,273, menunjukkan bahwa 27,3% variasi model dapat menentukan hasilnya. Diskusi lebih lanjut dan kesimpulan mengenai implikasi kontribusi teoritis dan praktis juga dibahas. Kata kunci: laporkitong; pengendalian yang dirasakan; kemudahan penggunaan yang dirasakan; kualitas yang dirasakan; model penerimaan teknologi